2022
DOI: 10.1186/s13071-022-05584-1
|View full text |Cite
|
Sign up to set email alerts
|

Activation of primary hepatic stellate cells and liver fibrosis induced by targeting TGF-β1/Smad signaling in schistosomiasis in mice

Abstract: Background In mice, liver fibrosis is the most serious pathologic change during Schistosoma japonicum (S. japonicum) infection. Schistosomiasis is mainly characterized by schistosome egg-induced granulomatous fibrosis. Hepatic stellate cells (HSCs) are mainly responsible for the net accumulation of collagens and fibrosis formation in the liver. Activated HSCs regulated by transforming growth factor-β1 (TGF-β1)/Smad signaling have emerged as the critical regulatory pathway in hepatitis virus or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…It has been revealed that HSCs regulated by the TGF-β1/Smad signaling pathway play an important role in liver fibrosis in S . japonicum -infected mice [ 75 ]. TGF-β is secreted by a variety of immune cells through the Smad pathway; further promoting the elevated levels of TIMP1, α-SMA, and collagen 1/2 during the HSC to myofibroblast transition, formatting and remodeling the ECM, and eventually leading to liver fibrosis [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been revealed that HSCs regulated by the TGF-β1/Smad signaling pathway play an important role in liver fibrosis in S . japonicum -infected mice [ 75 ]. TGF-β is secreted by a variety of immune cells through the Smad pathway; further promoting the elevated levels of TIMP1, α-SMA, and collagen 1/2 during the HSC to myofibroblast transition, formatting and remodeling the ECM, and eventually leading to liver fibrosis [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has the effects of activating hepatic stellate cells, promoting collagen synthesis, and ultimately leading to liver fibrosis [ 10 ]. There have been multiple reports on the relationship between liver fibrosis in schistosomiasis and TGF in hepatic stellate cells-β 1 /Smads signal transduction [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…The transforming growth factor-β (TGF-β) signaling pathway is extremely important for regulating mammalian T lymphocyte immune responses and is mainly dependent on Smad proteins to mediate signaling [ 14 ]. Type I receptor (TβR-I) and type II receptor (TβR-II) are the receptor proteins involved in the TGF-β signaling pathway [ 15 , 16 ]. TGF-β binds to TβR-I and TβR-II receptors to form complexes that trigger intracellular signaling.…”
Section: Introductionmentioning
confidence: 99%